Myocardin-related Transcription Factor Regulates Nox4 Protein Expression: LINKING CYTOSKELETAL ORGANIZATION TO REDOX STATE - Rozycki, Matthew (J Biol Chem, 2016)
TGFβ-induced expression of the NADPH oxidase Nox4 is essential for fibroblast-myofibroblast transition. Rho has been implicated in Nox4 regulation, but the underlying mechanisms are largely unknown. Myocardin-related transcription factor (MRTF), a Rho/actin polymerization-controlled coactivator of serum response factor, drives myofibroblast transition from various precursors. We have shown that TGFβ is necessary but insufficient for epithelial-myofibroblast transition in intact epithelia; the other prerequisite is the uncoupling of intercellular contacts, which induces Rho-dependent nuclear translocation of MRTF. Because the Nox4 promoter harbors a serum response factor/MRTF cis-element (CC(A/T)(6)GG box), we asked if MRTF (and thus cytoskeleton organization) could regulate Nox4 expression. We show that Nox4 protein is robustly induced in kidney tubular cells exclusively by combined application of contact uncoupling and TGFβ. Nox4 knockdown abrogates epithelial-myofibroblast transition-associated reactive oxygen species production. Laser capture microdissection reveals increased Nox4 expression in the tubular epithelium also during obstructive nephropathy. MRTF down-regulation/inhibition suppresses TGFβ/contact disruption-provoked Nox4 protein and mRNA expression, Nox4 promoter activation, and reactive oxygen species production. Mutation of the CC(A/T)(6)GG box eliminates the synergistic activation of the Nox4 promoter. Jasplakinolide-induced actin polymerization synergizes with TGFβ to facilitate MRTF-dependent Nox4 mRNA expression/promoter activation. Moreover, MRTF inhibition prevents Nox4 expression during TGFβ-induced fibroblast-myofibroblast transition as well. Although necessary, MRTF is insufficient; Nox4 expression also requires TGFβ-activated Smad3 and TAZ/YAP, two contact- and cytoskeleton-regulated Smad3-interacting coactivators. Down-regulation/inhibition of TAZ/YAP mitigates injury-induced epithelial Nox4 expression in vitro and in vivo. These findings uncover new MRTF- and TAZ/YAP-dependent mechanisms, which link cytoskeleton remodeling and redox state and impact epithelial plasticity and myofibroblast transition.